Women’s participation in political leadership: Standpoints from Central Asia and Central Europe - Lipovka, Anastassiya; Yerimpasheva, Aida; Rakhimbekova, Zhanar; Zakirova, Assem (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This article aims at determining the influence of power distribution within families on women’s views of politicians. The work represents the first cross-cultural study of gender stereotypes about political leaders embracing post-socialist Central Asian and Central European countries. The responses of 6,869 women to the Life in Transition Survey III were analyzed using a quantitative research study. A multivariate linear regression model and correlation coefficients allowed us to identify the relationship between patriarchal and patrilocal families with a high level of gender stereotypes and the impact of individual women’s decisions on their lower bias. No positive effect of spouses’ mutual decisions on the level of gender stereotypes was revealed. The theoretical importance of the work lies in expanding the existing knowledge about the influence of family power on women’s internal beliefs, which broadens the understanding of the Western Role Congruity Theory in emerging economies.